Methodology for forecasting in the Swedish–Norwegian market for el-certificates. (August 2015) - Wolfgang, Ove; Jaehnert, Stefan; Mo, Birger
Abstract: In this paper we describe a novel methodology for forecasting in the Swedish–Norwegian el-certificate market, which is a variant of a tradable green certificate scheme. For the forecasting, the el-certificate market is integrated in the electricity-market model EMPS, which has weekly to hourly time-step length, whereas the planning horizon can be several years. Strategies for the certificate inventory are calculated by stochastic dynamic programming, whereas penalty-rates for non-compliance during the annual settlement of certificates are determined endogenously. In the paper the methodology is described, and we show the performance of the model under different cases that can occur in the el-certificate market. The general results correspond to theoretical findings in previous studies for tradable green certificate markets, in particular that price-scenarios spread out in such a way that the unconditional expected value of certificates is relatively stable throughout the planning period. In addition the presented methodologies allows to assess the actual dynamics of the certificate price due to climatic uncertainty. Finally, special cases are indentified where the certificate price becomes excessively high respectively zero, due the design-specific dynamics of the penalty rate. Highlights: A method for forecasting in the Swedish–Norwegian el-certificate market is proposed. The developed model integrates the el-certificate and the power market. Banking of certificates and the endogenously calculated penalty rate are included. The certificate value is calculated using Stochastic-Dynamic-Programming. Price dynamics due to climatic weather uncertainties are assessed and illustrated.